Lexical Input in the Grammatical Expression of Stance: A Collexeme Analysis of the INTRODUCTORY IT PATTERN - Wang, Zhong; Fan, Weiwei; Fang, Alex Chengyu (Frontiers in Psychology, 2022)
Previous research on the INTRODUCTORY IT PATTERN unveiled various lexical and grammatical aspects of its use as a grammatical stance device, including the range of the pattern’s most frequently used adjectival or verbal stance lexemes, associated stance meanings, the most frequent sub-patterns, and the distinct uses in various contextual settings. However, the pattern’s stance meanings, which are deeply rooted in the associated lexical resources, are still understudied. This study explores the meanings of the INTRODUCTORY IT PATTERN by referring to the pattern’s stance meanings associated with the adjectival and verbal lexemes that are statistically attracted to the patterns. The research samples were extracted from the British component of the International Corpus of English (the ICE-GB). The samples were manually annotated for different stance types and a collexeme analysis was performed to identify the full range of stance lexemes statistically associated with the INTRODUCTORY IT PATTERN (collexemes). The results show that both adjectival and verbal collexemes are statistically and functionally significant for the delivery of discrete stance types/subtypes. Adjectival collexemes are frequently deployed for all four stance types: Epistemic stance, Evaluation, Dynamic stance, and Deontic stance, while verbal collexemes are valuable lexical resources for the Epistemic stance as their use entails modalized evidentiality, pointing to the epistemic necessity of events/propositions. Close examination of the use of adjectival and verbal collexemes identified three fundamental meanings of the INTRODUCTORY IT PATTERN. First, the pattern is inherently evaluative as it tends to attract more lexemes with evaluative meanings and associates evaluative meanings with superficially non-evaluative lexemes. Second, it features a scalarized expression of diversified stance types/subtypes, thus especially reflective of the scalarized semantic feature of stance expression. Third, it connotates an overwhelmingly positive likelihood judgment. The article concludes by discussing the limitations of this research.